Introduction: The entanglements of media and health in everyday life - Grønning, Anette; Sandberg, Helena (MedieKultur: Journal of media and communication research, 2023)
Just as the title above suggests, it is difficult to address health issues without considering the role of the media and everyday life; the time and space when health is produced and cared for or put at risk and exposed. In the introduction to this special issue, ‘Media and health in everyday life’, we will discuss the three components of the theme. We will offer some definitions, but also problematise the conceptual underpinnings and highlight the intertwinement of the three. We set off by reflecting on health. Then we will engage with ideas around the notion of everyday life. In the final section, we add the component of the media before we present and summarise the nine contributions to the special issue and clarify to what extent they add to our understanding of the theme.